The Role of Medical Rehabilitation: Management of Oromotor Dysfunction (Mechanical and Kinetic Movement Dysfunction) and Speech Therapy in Children with Cerebral Palsy - Anak Agung Ayu Niti Wedayani; Nurul Ullyani; Novia Andansari Putri Restuningdyah; Linda Silvana Sari; Aris Doyan (Postgraduate, University of Mataram, 2024)
Cerebral palsy (CP) is a non-progressive motor disorder caused by prenatal, perinatal, and postnatal factors, leading to movement and posture abnormalities. In Indonesia, around 0.60% of the total child population has CP (9 cases per 1000 live births). Speech and swallowing difficulties are common, affecting children’s nutritional status and development. Speech and oral motor therapy are effective in improving speaking and oromotor dysfunction. To determine the effectiveness of oromotor and speech therapy in improving swallowing, chewing, and speech abilities in children with CP. A case study was conducted at the